Migrants and City-Making Dispossession, Displacement, and Urban Regeneration - Çaglar, Ayse (Duke University Press, 2018)
In Migrants and City-Making Ayşe Çağlar and Nina Glick Schiller trace the participation of migrants in the unequal networks of power that connect their lives to regional, national, and global institutions. Grounding their work in comparative ethnographies of three cities struggling to regain their former standing - Mardin, Turkey; Manchester, New Hampshire; and Halle/Saale, Germany - Çağlar and Glick Schiller challenge common assumptions that migrants exist on society's periphery, threaten social cohesion, and require integration. Instead Çağlar and Glick Schiller explore their multifaceted role as city-makers, including their relationships to municipal officials, urban developers, political leaders, business owners, community organizers, and social justice movements.